1995
DOI: 10.1044/1058-0360.0402.37
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Visual Feedback to Elicit Correct /r/

Abstract: Biofeedback in the form of the visual display from the monitor of a real-time spectrograph was presented to a 10-year-old boy and a 14-year-old girl who had been unable to attain correct production of /r/ despite years of treatment. Both perceptual ratings and acoustic measures were made of the clients' productions of /r/ before and after treatment with the spectrograph. The results indicated that children and adolescents can use this type feedback to attain correct production of /r/ when other methods have fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 27 publications
(18 reference statements)
0
35
0
Order By: Relevance
“…For example, mirrors are often used to help patients see their own lip or jaw movements. Using the acoustic signal, spectral feedback has also been used to teach participants with speech disorders to achieve proper formant structure for vowels or rhotics (McAllister Byun & Hitchcock, 2012;Shuster, Ruscello, & Smith, 1992;Shuster, Ruscello, & Toth, 1995).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…For example, mirrors are often used to help patients see their own lip or jaw movements. Using the acoustic signal, spectral feedback has also been used to teach participants with speech disorders to achieve proper formant structure for vowels or rhotics (McAllister Byun & Hitchcock, 2012;Shuster, Ruscello, & Smith, 1992;Shuster, Ruscello, & Toth, 1995).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…It is not easy for children to comply with instructions regarding correct articulatory postures, especially in the case of /r/ and / 3^/ , sounds for which "there is little definitive tactile or kinesthetic feedback during production" (Shuster et al, 1995). A possiblc solution t o this problerrl is the use of the palatometer (such as the Model 6300 f' (~lr~lomrtrr.).…”
Section: Tools For Treatmentmentioning
confidence: 99%
“…Useful references include Borden, Harris, and Raphael (1994), Kent and Read (1992), Ladefoged (1996), andPicket (1980). Shuster, Ruscello, and Toth (1995) demonstrated the use of the Real-Tzme Spectrogram to elicit correct /r/ from two children, ages 10 and 14 years, both of whom had failed to learn /r/ after extensive periods of traditional therapy. First, the children were taught to identify the formants on the video display when the clinician produced a variety of vowels.…”
Section: Tools For Treatmentmentioning
confidence: 99%
“…Rhotics are distinguished acoustically from other sonorants by the low height of the third formant (F3), which closely approximates the second formant (F2). Both case studies (Shuster, Ruscello, & Smith, 1992;Shuster, Ruscello, & Toth, 1995) and single-subject experimental studies (McAllister Byun, 2017;McAllister Byun & Campbell, 2016;McAllister Byun, Halpin, & Szeredi, 2015;McAllister Byun & Hitchcock, 2012) have reported that visual-acoustic biofeedback featuring a lowered F3 target can improve rhotic production in speakers who have not responded to other forms of intervention. One caution that has been raised in previous studies of various types of biofeedback (e.g., Gibbon & Paterson, 2006;McAllister Byun & Hitchcock, 2012;Preston et al, 2014) is that gains made in the treatment setting do not automatically generalize to contexts in which enhanced feedback is not available.…”
mentioning
confidence: 99%